Palladium(0)-Catalyzed Difunctionalization of 1,3-Dienes: From Racemic to Enantioselective - Wu, Xiang; Gong, Liu-Zhu (Synthesis, 2019)
1,3-Dienes are easily accessible chemicals that participate in a series of reactions acting on the carbon–carbon double bonds. Catalytic difunctionalization of 1,3-dienes provides a wide scope of functionalized chemicals. Pd(0) catalysts provide a diverse set of principles for the creation of asymmetric catalytic reactions, which are initiated with the oxidative addition and then undergo insertion reaction with one of double bonds of the 1,3-diene to become a π-allyl palladium species that is reactive toward nucleophilic attack. This review summarizes typical advances on the Pd(0)-catalyzed difunctionalization of 1,3-dienes in recent decades, particularly emphasizing the concepts that enable the switch from a racemic reaction to an enantioselective version.1 Introduction2 Amination3 Boration4 Carbonation5 Hydrogenation6 Oxygenation7 Silylation8 Conclusion and Outlook
Keywords: palladium(0); asymmetric catalysis; difunctionalization; 1,3-dienes; cascade reaction